Chemical suitability of groundwater for irrigation in Trimohoni and Sagardari union, Keshabpur Upazila, Jessore, Bangladesh (Bangladesh Journal of Scientific Research, 2016)
The paper intends to provide guidance to evaluate and identify a standard ground water chemistry data for irrigation in south western region of Bangladesh. During the course of hydrogeological studies in the study area, twenty water samples were collected from twenty different villages and chemically analyzed. The analytical results revealed that the water was slightly acidic to slightly alkaline (pH 6.68 - 7.32) and TDS values range from 565 to 1073 mg/l. The other parameters like sodium adsorption ratio, (SAR) (0.10 - 0.27), sodium percentage (3.22 - 7.13), residual sodium carbonate, (RSC) (3.2 - 5.33) and potential soil salinity, (PS) (less than 30) were below the desired limit suggesting the suitability for irrigation purpose. Considering SAR, permeability index and salinity hazard, all waters could be applied safely for irrigation without any hazard to crops.Bangladesh J. Sci. Res. 27(2): 121-131, December-2014